Sustainability strategy in malang regency :analitycal hierarchy process approach - Nurhayati, Yetty; Pudjihardjo, Pudjihardjo; Susilo, Susilo; Ekawaty, Marlina (Journal of Business on Hospitality and Tourism, 2022)
The development of tourism has led to the emergence of various types of attractions; one of them is a tourist village which is expected to improve the welfare of the local community. Malang Regency has several tourist villages with various potentials. Pujon Kidul, Sanankerto, and Gubugklakah are villages that carry the concept of sustainable tourism. The purpose of this research is to improve its economic sustainability status. The method used is the AHP test. The results showed that the best strategy for Pujon Kidul village was to develop a strawberry picking tourist attraction, while for Sanankerto it was the addition of new tour packages related to water tourism and for Gubugklakah village was the development of Mount Bromo tour packages.